Analisis Penentuan Tarif Sewa Kamar Hotel Dengan Metode Activity-Based Costing (ABC) Pada Hotel Gajah Mada Lumajang - Laili Nurul Afiva; Sri Kantun; Tiara Tiara (JURNAL PUNDI, 2023)
Along with the increase in service companies, especially in the hotel business sector, there is competition. The business strategy that can be carried out by hotel management in winning the competition is to provide the best facilities and services to hotel guests. Therefore, it takes the right calculation in determining room rental rates. The activity-based costing (ABC) method is very effective for determining room rental rates, because it provides an accurate and efficient calculation by calculating the costs incurred as a result of the provision of facilities, so it can help reduce cost deviations. This study aims to analyze the determination of hotel room rental rates using the activity-based costing (ABC) method at Gajah Mada Hotel Lumajang. This type of research is descriptive with a quantitative approach. The results obtained are that the hotel room rental rates carried out by Gajah Mada Lumajang Hotel have a greater value compared to hotel room rental rates using the activity-based costing (ABC) method, namely with a difference in room rental rates of IDR 14,117.00 for room types garden suite room, and IDR 8,096.00 for the executive suite room type. This difference in results is experiencing overcosting.